Spotlight on International Funders’ Commitments to Financial Inclusion - Lahaye, Estelle; Dashi, Edlira; Dolke, Eda; Soursourian, Matthew (World Bank, Washington, DC, 2015)
Although international funders have been longstanding supporters of financial inclusion, their commitments have been put to the test in the past five years. The financial crisis led to a more challenging economic environment and budget cuts at public donor agencies. Results of impact studies made the expectations of microfinance more realistic. Yet, international funding continues to grow. In 2013, international funders committed at least 31 billion dollars to support financial inclusion - an estimated increase of 7 percent on average per year between 2011 and 2013. This brief analyzes trends in the international funding landscape based on consultative group to assist the poor (CGAP) research.